2021
DOI: 10.1038/s41366-021-00910-6
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer after bariatric surgery (Cric-Abs 2020): Sicob (Italian society of obesity surgery) endorsed national survey

Abstract: BACKGROUND:The published colorectal cancer (CRC) outcomes after bariatric surgery (BS) are conflicting, with some anecdotal studies reporting increased risks. The present nationwide survey CRIC-ABS 2020 (Colo-Rectal Cancer Incidence-After Bariatric Surgery-2020), endorsed by the Italian Society of Obesity Surgery (SICOB), aims to report its incidence in Italy after BS, comparing the two commonest laparoscopic procedures-Sleeve Gastrectomy (SG) and Roux-en-Y gastric bypass (GBP). METHODS: Two online questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The French population study also reported that the same age group of obese patients who did not undergo bariatric surgery have a 34% higher risk of developing CRC compared to patients who have undergone bariatric surgery. A similar observation of the reduced risk of developing CRC after bariatric surgery was reported in the population studies of Italy [ 56 ], England [ 57 ], and the US [ 58 , 59 ]. Furthermore, a meta-analysis study by an Australian research team found that obesity in young adults, especially increased weight change at a young age from early adulthood to midlife, is associated with a higher risk of CRC than those who develop obesity at an older age from midlife to old age [ 60 ].…”
Section: Sex-dependent Differences In Obesity-associated Crcsupporting
confidence: 79%
“…The French population study also reported that the same age group of obese patients who did not undergo bariatric surgery have a 34% higher risk of developing CRC compared to patients who have undergone bariatric surgery. A similar observation of the reduced risk of developing CRC after bariatric surgery was reported in the population studies of Italy [ 56 ], England [ 57 ], and the US [ 58 , 59 ]. Furthermore, a meta-analysis study by an Australian research team found that obesity in young adults, especially increased weight change at a young age from early adulthood to midlife, is associated with a higher risk of CRC than those who develop obesity at an older age from midlife to old age [ 60 ].…”
Section: Sex-dependent Differences In Obesity-associated Crcsupporting
confidence: 79%
“…As shown in Figure 1 , we included 18 [ 2 , 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] studies in the quantitative and qualitative analysis. A meta-analysis was conducted on 12,517,893 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the increased prevalence of obesity has caused an increase even in the prevalence of colorectal cancers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%